Dealership e-Commerce package (e-Payment system) / Ooi Chon Hui - Ooi , Chon Hui (2002)
The purpose of this project is to curry out a critical research and to gather all the relevant information regarding a specific e-payment system. Appropriately. the detail information will simultaneously cover the protocol that has been used by the specific e-payment system. Hence, this project will focus on an electronic payment protocol named Secure Electronic Transaction or SET and it shall emphasize particularly on the security aspect provided by the above mention protocol. The result from the research will be presented in an Internet to provide a comprehensive and thought information on the subject. This Dealership E-Commerce Package wills allows users who know nothing about the e-payment system to understand how actually online transactions occur. In this respect, the user will also get a better understanding about this e-payment system especially about all the processes that are look place before the transactions. Finally, they will also be acknowledged on the security provided by FT and thus can confide them to feel secure when using their credit payment facility over the Internet. The successful of this e-payment system development will widen the usage of the formal on line system and produce an intelligent of electronic payment application that will expose the electronic payment possibility for the future trend.